Fungsi dan Makna Paon bagi Masyarakat Banjar Cekeng di Desa Sulahan, Bangli - Purnama, Ida Bagus Putu Adhi; Sudiarna, I Gusti Putu; Kaler, I Ketut (Sunari Penjor : Journal of Anthropology, 2022)
The Bajar Cekeng community, Sulahan Village, Bangli District has a Paon building or kitchen that is different from the Paon layout in general. Every traditional house in Banjar Cekeng, Sulahan Village has a Paon which is located to the right of the sanggah or place of worship as its uniqueness. This study aims to determine the function of Paon in the traditional house of Banjar Cekeng, Sulahan, Susut, Bangli. This study uses qualitative methods emphasizing descriptive and interpretative, using functional and interpretive theory. Paon for the people of Banjar Cekeng serves as a place to cook rice, water, snacks and other foods, and can be used as a bed if you don't have a building to sleep in, usually those who sleep in Paon are pelingsir (elders). Paon is interpreted as unifying energy with each other as well as a reflection of family life.